Cultural Heritage in Modern Kurdish Poetry: Reading Kakey Falah’s Work as a Case Study - Farhad Ghader Karim (پژوهشنامه ادبیات کردی, 2020)
National heritage has always been an important resource for modern Kurdish poets. This stems from the belief that many internal, social, intellectual, political, and even educational aspects of the Kurdish people are demonstrated within their national heritage. These aspects are deeply rooted in the nation, expressed in a simple language, and nationally accepted. As one of the modernist Kurdish poets, Kakey Falah understood the importance of this national capital, and according to the content and concepts of his poems, tried to make use of the different aspects of this heritage such as proverbs and idioms, legend, poetry, story, songs, tradition, etc. Connecting his era to the past, he highlighted the fact that the present is the linking chain of the past and the future. For this reason, the present research seeks to show the quality and quantity of the poet’s trade with the national heritage.